Bisnes satu cabang jihad - Mohd. Ali Hj. Hashim (Cheras, Kuala Lumpur : Utusan Publications & Distributors, 2003)
Business management and entrepreneurship in Malaysia from Islamic viewpoint.
buku 1. Pembudayaan bisnes untuk survival
Includes bibliographical references (v. 1, p. 232-235) and index.
In Malay.
Keywords: Industrial management -- Malaysia; Entrepreneurship -- Malaysia; Islam -- Economic aspects -- Malaysia